The Influence of Instagram Marketing on Colleges on Post Interaction - Masrufah Masrufah; Arif Hartono (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The ease of using social media today makes many universities use social media as part of their marketing strategy such as Instagram marketing. The purpose of this study was to analyze the effect of Instagram marketing on the interaction of posting at universities at the Islamic University of Indonesia. Instagram marketing can be evaluated based on post typology, namely advertising, event, information, entertainment, and achievement. The analysis used multiple regression analysis with OLS estimation from 330 posts on the Instagram of the Islamic University of Indonesia in a twelve-month period using the SPSS application program. This study aims to help identify which variables can generate greater interaction between users, and provide strategic suggestions for marketing management on social networks. The results of the data analysis show (1) Advertising has no effect on the interaction of posting (2) Events have no effect on the interaction of posting (3) Entertainment has a positive effect on the interaction of posting (4) achievement has an effect on the interaction of posting on likes but does not have an effect on the interaction of posting on comments.